PERANCANGAN SISTEM INFORMASI E-COMMERCE MENGGUNAKAN FRAMEWORK CODEIGNETER DI CV. AL-FITHRAH KOTA PADANG - Irna Gusmawati; Legiman Slamet (Universitas Negeri Padang, 2019)
The development of information and communication technology that is rapidly developing throughout the world opens up new opportunities for businesses to reach sales throughout the region. CV. Al-Fithrah is an Islamic business company that provides Muslim and Muslim equipment, such as Islamic books, Muslim fashion / quality herbs. This design is made to help it easier in the management process, sales reports and promote products to consumers, so that it can improve the quality of sales and make it easier to process sales data. System design is described in four stages; namely use case diagrams, statechart diagrams, activity diagrams and sequence diagrams. The design of this E-Commerce information system is made using the PHP programming language with the CodeIgniter and MySql framework. This sales information system has facilities for admin users, owners, operators, warehouses and consumers. So that this system displays products that are sold and facilitates communication between the seller and the buyer and can produce useful information for CV.Al-Fithrah. Keyword : Information System, E-commerce, PHP, MySql, CodeIgniter